Redescription of Conniella apterygia Allen and its reassignment in the genus Cirrhilabrus Temminck and Schlegel (Teleostei: Labridae), with comments on cirrhilabrin pelvic morphology - Tea, Yi-Kai; Allen, Gerald R.; Goatley, Christopher H. R.; Gill, Anthony C.; Frable, Benjamin W. (Zootaxa, 2021)
Conniella apterygia is redescribed from re-examination of the holotype, two paratypes, and six additional specimens. The genus is closely allied to Cirrhilabrus, sharing similarities in general morphological and meristic details, but is separated from Cirrhilabrus and most other labrid fishes in lacking pelvic fins and a pelvic girdle. Recent molecular phylogenetic studies have provided strong evidence for the deep nesting of Conniella within Cirrhilabrus, contradicting its generic validity and suggesting that the loss of pelvic elements is autapomorphic. Consequently, the species is redescribed and assigned to the genus Cirrhilabrus, as Cirrhilabrus apterygia new combination. The pelvic morphologies of related cirrhilabrin labrids are discussed, and a new synapomorphy is identified for Paracheilinus.